Fine Mapping and Candidate Gene Identification of a White Flower Gene BrWF3 in Chinese Cabbage (Brassica rapa L. ssp. pekinensis) - Yang, Shuangjuan; Tian, Xinxin; Wang, Zhiyong; Wei, Xiaochun; Zhao, Yanyan; Su, Henan; Zhao, Xiaobin; Tian, Baoming; Yuan, Yuxiang; Zhang, Xiao-Wei (Frontiers in Plant Science, 2021)
Flower color is an important trait in plants. However, genes responsible for the white flower trait in Chinese cabbage are rarely reported. In this study, we constructed an F2 population derived from the Y640-288 (white flower) and Y641-87 (yellow flower) lines for the fine mapping of the white flower gene BrWF3 in Chinese cabbage. Genetic analysis indicated that BrWF3 was controlled by a single recessive gene. Using BSA-seq and KASP assays, BrWF3 was fine-mapped to an interval of 105.6 kb. Functional annotation, expression profiling and sequence variation analyses confirmed that the AtPES2 homolog, Bra032957, was the most promising candidate gene for BrWF3. Carotenoid profiles and transmission electron microscopy analysis suggested that BrWF3 might participate in the production of xanthophyll esters (particularly violaxanthin esters), which in turn disrupt chromoplast development and the formation of plastoglobules (PGs). A SNP deletion in the third exon of BrWF3 caused the loss of protein function, and interfered with the normal assembly of PGs, which was associated with reduced expression levels of genes involved in carotenoid metabolism. Furthermore, we developed and validated the functional marker TXBH83 for BrWF3. Our results provide insight into the molecular mechanism underlying flower color pigmentation and reveal valuable information for marker-assisted selection (MAS) breeding in Chinese cabbage.